Design of a wideband array antenna - Zhang, Yan (2013)
This thesis presents a design of wide-band and high-gain linear array antenna which has eight antenna elements. The array antenna can operate at the frequency ranging from 890MHz to 2500MHz, and radiate or receive vertically polarized waves covering a sectored range of 120° in the azimuth plane. The simulated gain of the array antenna is over 10dBi in the whole frequency band covering the entire sector. The simulated return loss of the array antenna fed by a T-junction power divider is better than 10dBi over the entire frequency range. This array antenna should be useful for base stations serving wide-range mobile users and can be readily scaled to other ultra-wideband applications.